Ceftaroline fosamil in the treatment of methicillin-resistant Staphylococcus aureus - P., Sahad; D., Chandrakala; K., Meghana; Gowda, Medhini H. (International Journal of Research in Medical Sciences, 2024)
Ceftaroline fosamil, a cephalosporin approved by the FDA for treating infections caused by methicillin-resistant Staphylococcus aureus (MRSA). Staphylococcus aureus, particularly MRSA strains, poses a significant health risk due to antibiotic resistance. Ceftaroline fosamil is unique in its ability to bind to penicillin-binding protein 2a (PBP2a) found in MRSA, inhibiting bacterial cell wall synthesis and causing bacterial death. The pharmacokinetics of ceftaroline involve rapid conversion to its active form, primarily excretion through the kidneys, and a plasma protein binding rate of approximately 20%. Ceftaroline is effective against complex skin and soft tissue infections (cSSTIs) and community-acquired pneumonia (CAP), especially when MRSA is suspected. However, its efficacy against gram-negative bacteria is limited. The safety profile of ceftaroline fosamil is generally good, with reported adverse events comparable to other comparator agents in clinical trials. It is contraindicated in individuals with hypersensitivity to cephalosporins. Comparative efficacy with other antibiotics like vancomycin and daptomycin is discussed, emphasizing the importance of considering individual patient characteristics and local prevalence of resistant bacteria. The use of ceftaroline fosamil in special populations, such as pediatric and adult patients. While its efficacy in pediatric MRSA infections is explored, the lack of large-scale clinical trials for certain conditions like MRSA bacteremia is acknowledged. Clinical outcomes, including successful treatment of MRSA bacteremia, infective endocarditis, central nervous system infections, and nosocomial pneumonia, are discussed, suggesting ceftaroline fosamil's potential as a valuable therapeutic option. The conclusion underscores its breakthrough status, offering hope in addressing MRSA infections and improving patient outcomes.